Strengthening global diversity characters through the P5 theme of local wisdom in the independent curriculum at SMPN 1 Ngoro Mojokerto - Rohmatulloh, Nia Lorenda; Lutfiana, Rose Fitria; Widodo, Rohmad (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2026)
Indonesia's cultural diversity is a wealth as well as a national identity that needs to be strengthened through education. One of the efforts made is through the implementation of the Pancasila Student Profile Strengthening Project (P5) with the theme of local wisdom in the Independent Curriculum. This study aims to analyze the implementation of P5 based on local wisdom in strengthening the character of global diversity in students at SMP Negeri 1 Ngoro Mojokerto. This study uses a descriptive qualitative approach with data collection techniques in the form of observation, semi-structured interviews, and documentation. The research informants consisted of school principals, P5 coordinating teachers, and students in grades VII and VIII. Data were analyzed using Miles and Huberman's interactive model which included data reduction, data presentation, and conclusion drawn. The results of the study show that the implementation of P5 through exploration of local culture, cultural practices, creative creation, and participation in the Tapestry Festival is able to strengthen the global diversity character of students. This strengthening is reflected in the ability of students to know and appreciate local culture, be open to diversity, and develop communication and cooperation in project activities. Project-based learning that integrates local wisdom provides a contextual and meaningful learning experience for students. Thus, the implementation of P5 based on local wisdom can be an effective strategy in shaping the character of global diversity in students.